Diagnosis of Li-Fraumeni syndrome: Differentiating TP53 germline mutations from clonal hematopoiesis : Results of the observational AGO-TR1 trial - Weber-Lassalle, Konstantin; Marmé, Frederik (Human mutation, 2018)
The Li-Fraumeni cancer predisposition syndrome (LFS1) presents with a variety of tumor types and the TP53 gene is covered by most diagnostic cancer gene panels. We demonstrate that deleterious TP53 variants identified in blood-derived DNA of 523 patients with ovarian cancer (AGO-TR1 trial) were not causal for the patients' ovarian cancer in three out of six TP53-positive cases. In three out of six patients, deleterious TP53 mutations were identified with low variant fractions in blood-derived DNA but not in the tumor of the patient seeking advice. The analysis of the TP53 and PPM1D genes, both intimately involved in chemotherapy-induced and/or age-related clonal hematopoiesis (CH), in 523 patients and 1,053 age-matched female control individuals revealed that CH represents a frequent event following chemotherapy, affecting 26 of the 523 patients enrolled (5.0%). Considering that TP53 mutations may arise from chemotherapy-induced CH, our findings help to avoid false-positive genetic diagnoses of LFS1.
Gesehen am 01.07.2019